Case report: Neuroendocrine breast carcinoma with a germline EGFR T790M mutation - Sagan, Olivia A.; Rothstein, Anna; Jambunathan, Bhaghyasree; Hadziahmetovic, Mersiha; Antoniolli, Anita; Rashid, M. Hammad (Frontiers in Oncology, 2023)
Background The epidermal growth factor receptor (EGFR) p.Thr790Met (T790M) mutation was discovered as a resistance mechanism in patients with lung cancer treated with first- and second-generation tyrosine kinase inhibitors. Further studies revealed the EGFR T790M mutation in treatment-naive non-small cell lung carcinoma (NSCLC) and as a rare germline mutation strongly associated with NSCLC. Somatic EGFR T790M mutations have been reported in a limited population of patients with triple-negative breast cancer. There are no previous reports of a germline EGFR T790M mutation found in a patient with breast cancer. Case presentation We present a rare case of a 42-year-old woman with a rapidly progressing 8 cm mass in the right lateral breast. An additional right breast mass with multiple lymph nodes characteristic or suspicious of metastasis was found. Ultrasound-guided biopsy showed high-grade, poorly differentiated invasive neuroendocrine carcinoma of the right breast and metastatic carcinoma of a right axillary lymph node. Genetic testing revealed a germline EGFR T790M mutation. The patient underwent neoadjuvant chemotherapy, right mastectomy with lymph node dissection, adjuvant radiation to the right chest wall and axilla, and adjuvant chemotherapy. Conclusion This is the first reported case of a patient with high-grade neuroendocrine carcinoma, triple-negative breast cancer and a germline EGFR T790M mutation. Further investigation is needed to find a possible correlation between the cancer in this patient and her mutation. Since there are no current guidelines, further research is also needed to define screening protocols for patients with germline EGFR T790M mutations. Additional treatment options and cancer risk could also be found with further research, which would benefit all patients with a germline EGFR T790M mutation.